DEVELOPING TASK-BASED ENGLISH TEACHING MATERIALS FOR BUSINESS AND MANAGEMENT VOCATIONAL HIGH SCHOOL - Sallem, Christina; Sutapa, Gatot; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This study was conducted on three objectives. They include exploring the studentsâ€™ needs for English teaching materials for accounting, designing and writing needs-based materials, and evaluating the applicability of developed model of materials. This research was a developmental research. The subjects of this research were English teacher, Accounting teacher, and 28 students of Year-11 of Accounting department of SMK Filadelfia Pemangkat. Various Â records of needs assessment indicated that there was a high demand for materials of English for accounting. Moreover, a gap was found between the content of KTSP English syllabus with the studentsâ€™ needs. The findings on materials writing and implementation revealed that the materialsâ€™ applicability is proven â€œexcellentâ€ according to the usersâ€™ perspectives. The materials were considered helpful and relevant with the studentsâ€™ needs as it provided specific English materials and meaningful activities which connected the English classroom learning with the real world use of English for Accounting. Keywords: Developing materials, task-based materials, English for accounting Abstrak: Penelitian ini dilaksanakan untuk mencapai 3 tujuan, yaitu untuk mengetahui kebutuhan siswa terhadap materi pengajaran bahasa Inggris akuntansi, untuk merancang dan menulis materi berdasarkan kebutuhan tersebut, dan untuk mengevaluasi daya terap materi pengajaran bahasa Inggris akuntansi yang telah dikembangkan. Penelitian ini merupakan sebuah penelitian pengembangan dengan subyek penelitian yang terdiri dari seorang guru bahasa Inggris, seorang guru akuntansi, dan 28 siswa kelas 11 jurusan akuntansi di SMK Filadelfia Pemangkat. Sejumlah data analisis kebutuhan yang terkumpul mengindikasikan bahwa terdapat kebutuhan yang tinggi terhadap materi pengajaran bahasa Inggris akuntansi. Selain itu, terdapat kesenjangan antara isi silabus KTSP bahasa Inggris denganÂ  kebutuhan siswa sebenarnya. Berdasarkan perspektif penggunanya, materi yang telah dikembangkan dan diujicoba dinilai â€œsangat baikâ€. Materi tersebut dianggap membantu dan sesuaiÂ  dengan kebutuhan siswa karena menyediakan materi bahasa Inggris yang khusus dan aktifitas yang bermakna yang menghubungkan pembelajaran bahsa Inggris di kelas dengan kegunaan bahasa Inggris untuk akuntansi di dunia nyata. Kata kunci: Pengembangan materi, berbasis tugas, Â akuntansi